2018
DOI: 10.1103/physreve.97.022123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of turbulent mixing on critical behavior of directed percolation process: Effect of compressibility

Abstract: Universal behavior is a typical emergent feature of critical systems. A paramount model of the nonequilibrium critical behavior is the directed bond percolation process that exhibits an active-to-absorbing state phase transition in the vicinity of a percolation threshold. Fluctuations of the ambient environment might affect or destroy the universality properties completely. In this work, we assume that the random environment can be described by means of compressible velocity fluctuations. Using field-theoretic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 77 publications
(172 reference statements)
0
4
0
Order By: Relevance
“…In (3) the irreducible part is explicitly written as a separate term and contains the space dimension three in the coefficient of the Kronecker symbol. In d dimensions the coefficient is thus 2/d instead of 2/3 used -quite surprisingly -in earlier work [10,11,12,13,14]. This is reflected in the connection between the dynamic viscosities η and ζ on one hand and kinematic viscosities µ and ν on the other.…”
Section: Hydrodynamic Equations In D Dimensionsmentioning
confidence: 91%
See 3 more Smart Citations
“…In (3) the irreducible part is explicitly written as a separate term and contains the space dimension three in the coefficient of the Kronecker symbol. In d dimensions the coefficient is thus 2/d instead of 2/3 used -quite surprisingly -in earlier work [10,11,12,13,14]. This is reflected in the connection between the dynamic viscosities η and ζ on one hand and kinematic viscosities µ and ν on the other.…”
Section: Hydrodynamic Equations In D Dimensionsmentioning
confidence: 91%
“…which leads to the model used in the earlier RG analyses of compressible fluid [11,12,13,14]. In the next section it will be shown that this is not the model suitable for description of perfect gas.…”
Section: Randomly Stirred Barotropic Fluidmentioning
confidence: 99%
See 2 more Smart Citations